The apple orchard - Wiggs, Susan (Don Mills, Ont. : Harlequin Mira, 2013)
Set to inherit half of Bella Vista, an apple orchard in a town called Archangel, along with a half-sister she's never heard of, Tess Delaney, discovers a world filled with the simple pleasures of food and family.
Includes recipes.
Keywords: Apple growers -- Fiction; Family secrets -- Fiction; Inheritance and succession -- Fiction; Orchards -- Fiction; Sisters -- Fiction; Female friendship -- Fiction; Memory -- Fiction